A SWOT BASED ANALYSIS FOR PROMOTING SUSTAINABLE JOB SATISFACTION IN CANADA - Emmanuel Imuede OYASOR; Adedeji Daniel GBADEBO (Association of Social and Educational Innovation, 2024)
The main objective of the article is analyzed the framework in promoting sustainable job satisfaction in a Canada. In doing this, we identify the issues affecting the growth and development of the firm in the financial industry in Canada. Specifically, we consider the National Best Financial Network (NBFN), which is a unique and ground-breaking network of financial professionals with collaborative team spirit to provide best-in-class products and services to their clients. We employ a descriptive approach based on the Porter's five factors approach to review the situational analysis aimed at giving a clear picture of both the internal and external environment of the business and the SWOT analysis to examine the situation for the strategic decision and attainment of the objectives. We find amongst other the existence of multicultural and cross-country issues. These issues could be cultural and regulatory concerns and demand preference or other related issues that can stand in the expansion path of National Best into other countries. Also, the operational risk of international expansion like cultural differences, volatility of economic variables, political uncertainties and other indeterminacies that can affect the operation of the business. Thus, we recommend possible long-term and short-term solutions.